EagI and NotI linking clones from human chromosomes 11 and Xp. - Pook, M; Thakrar, R; Pottinger, B; Harding, B; Porteous, D; van Heyningen, V; Cowell, J; Jones, C; Povey, S; Davies, K; Thakker, R (1996)
EagI and NotI linking libraries were prepared in the lambda vector, EMBL5, from the mouse-human somatic cell hybrid 1W1LA4.9, which contains human chromosomes 11 and Xp as the only human component. Individual clones containing human DNA were isolated by their ability to hybridise with total human DNA and digested with SalI and EcoRI to identify the human insert size and single-copy fragments. The mean (+/- SD) insert sizes of the EagI and NotI clones were 18.3 +/- 3.2 kb and 16.6 +/- 3.6 kb, respectively. Regional localisation of 66 clones (52 EagI, 14 NotI) was achieved using a panel of 20 somatic cell hybrids that contained different overlapping deletions of chromosomes 11 or Xp. Thirty-nine clones (36 EagI, 3 NotI) were localised to chromosome 11; 17 of these were clustered in 11q13 and another nine were clustered in 11q14-q23.1. Twenty-seven clones (16 EagI, 11 NotI) were localised to Xp and 10 of these were clustered in Xp11. The 66 clones were assessed for seven different microsatellite repetitive sequences; restriction fragment length polymorphisms for five clones from 11q13 were also identified. These EagI and NotI clones, which supplement those previously mapped to chromosome 11 and Xp, should facilitate the generation of more detailed maps and the identification of genes that are associated with CpG-rich islands.